Accounting Structure of Thebalance Sheet of Listed Companies in Croatia - Roška, Vlasta (Studia Oeconomica Posnaniensia, 2019)
The balance sheet is one of the bases of a financial statement. A balance sheet provides information that helps managers and investors evaluate a company's assets and ability to achieve its primary goals of profitability and solvency. The main aim of this research is confirmed that listed companies in Croatia are successfully recovering after the World economic crisis and increasing their as-sets and their strength. The research was conducted on the financial statements of listed companies on the Zagreb Stock Exchange for 2008, 2012 and 2017. The study shows that the listed companies in Croatia increased their assets, but the structure is traditionally the same, in favour of tangible assets in the researched period.